Marketing Plan of Lemigas Product as Public Service Agency (BLU) (Case: Lain Air Gun Seismic) - Islami, Dian; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2018)
Abstract - The Ministry of Energy and Mineral Resources (EMR) is obliged to realize energy sovereignty for the future which includes access to development, availability, capability and competitiveness. Based on World Economic Forum data, Global Competitiveness Index 2016 - 2017, Indonesia is ranked 41 out of 138 other countries. An achievement that lags far behind other countries in Asia. Technological readiness, innovation and business sophistication should receive attention. Furthermore, corruption and inefficient government bureaucracy are the most problematic factor in doing business in Indonesia. In order to improve services to the community and in line with the desire to change the externality of bureaucracy in the Ministry of EMR, the Minister of EMR Ignasius Jonan assigned the Research and Development Agency (Balitbang) to the Public Service Agency (BLU). Turning bureaucracy into a corporation is the goal of shifting the organization's functions. Lemigas as part of an institution in Balitbang that has previously implemented BLU financial management. However, it has not significantly shown an increase in service and revenue for the institution. Land Mini Airgun which became one of Lemigas's flagship product requires a marketing approach to improve its marketing. Land Mini Airgun serves as a seismic tool on land that can replace seismic functions that use explosives that have been used and not environmentally friendly. However, the opposite is conveyed by competitor which also have seismic services that Land Mini Airgun could not replace the existing seismic function because Land Mini Airgun is as an additional tool if in one seismic work encountered swamp or river area to keep the integrity of the data then used the tool. This research uses marketing management theory and marketing mix approach to know marketing plan to Land Mini Airgun. This study also used the analysis of Porter Five Forces, PESTEL, SWOT as an analysis tool. This study uses qualitative methods by interviewing several oil and gas service companies to offer products as well as make comparisons. Interviews are also conducted on internal Balitbang to find out what has been done to conduct marketing plans and cooperation schemes that have been there so far whether still needed or not. The purpose of this research is to give recommendation to Lemigas to do marketing plan of Land Mini Airgun in order to increase cooperation interest by consumer side. Keywords: Seismic, Land Mini Airgun, Public Service Agency, Marketing Plan